2018
DOI: 10.3917/anso.182.0341
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction With Work-Life Balance: Couples with Egalitarian Practices in their Transition to First-Time Parenthood in Spain

Abstract: This study analyses dual-earner couples' subjective satisfaction with work-life balance after having their first child. We draw on a longitudinal qualitative analysis of 31 Spanish couples who showed an egalitarian division of housework prior to childbirth.Participating couples were interviewed during pregnancy and about 18 months after the birth. We analysed individuals' subjective feelings of satisfaction with the way that childcare was organised. The study reveals that half of the couples moved towards a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…Several studies in the review found that associations between their independent variable and higher-order parity intentions/outcomes disappeared when examining desire for or outcome of a first child, lending support to this theory (Park et al 2010;Komatsu 2011;Goldscheider et al 2013;Harknett et al 2014;Lee and Hwang 2017;Freeman Figure 3 Matching study types to the part of the gender revolution U-shaped curve that they measure et al 2018; Puur et al 2018). This is logical, given that domestic load is known to increase with the presence of a child (Craig and Bittman 2008), and that childcare is more likely to be performed by the woman, even if the couple had a gender equal distribution of domestic work before the birth (González et al 2018). Another clear finding is that the majority of these analyses reporting a negative or mixed association used gender role attitudes as their explanatory variable (19 of 26).…”
Section: Discussionmentioning
confidence: 97%
“…Several studies in the review found that associations between their independent variable and higher-order parity intentions/outcomes disappeared when examining desire for or outcome of a first child, lending support to this theory (Park et al 2010;Komatsu 2011;Goldscheider et al 2013;Harknett et al 2014;Lee and Hwang 2017;Freeman Figure 3 Matching study types to the part of the gender revolution U-shaped curve that they measure et al 2018; Puur et al 2018). This is logical, given that domestic load is known to increase with the presence of a child (Craig and Bittman 2008), and that childcare is more likely to be performed by the woman, even if the couple had a gender equal distribution of domestic work before the birth (González et al 2018). Another clear finding is that the majority of these analyses reporting a negative or mixed association used gender role attitudes as their explanatory variable (19 of 26).…”
Section: Discussionmentioning
confidence: 97%
“…People experience role conflict when they find themselves pulled in various directions as they try to respond to the many statuses they hold. Role conflict theory posits that 'individuals have limited time and energy and adding extra roles and responsibilities necessarily creates tension between competing demands and a sense of overload and inter-role conflicts (Marshall & Barnett, 1993;González, Lapuerta, Martín-García & Seiz, 2018). The theory explains that commitment to multiple roles can lead to incompatible and/or excessive role expectations, which in turn can lead to physical and mental disequilibria (Fowlkes, 1987;Ward, 2004).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Así, el debate sobre las implicaciones de la reversión del gap educativo permanece abierto (Van Bavel, Schwartz y Esteve 2018). Mientras que algunas investigaciones sostienen que el aumento de la hipogamia será fuerte y ayudará a que las mujeres logren mayor poder económico e igualdad en términos de conciliación (Klesment y Van Bavel 2017;González et al 2018), otras argumentan que el grado de convergencia hacia la simetría de género es insuficiente o se ha estancado (England 2010). En el caso español, el fuerte peso de los equilibrios tradicionales podría frenar ese crecimiento para algunos grupos poblacionales (Esping-Andersen et al 2013).…”
Section: Introductionunclassified